Pentingnya Pengukuran Pupil Distance (PD) Secara Tepat Untuk Menjaga Akurasi Distance Vitror (DV) Kacamata - Toma Toma; Bunyamin Rizki Abdillah; Murni Marlina Simarmata (Jurnal Mata Optik, 2021)
Pupil Distance (PD) is measured in millimetres and even a slight variation can cause a number of vision and eye health problems due to inacurately fitting of Distance Vitror (DV). PD must be paralel to DV, therefore PD measurements must be committed throughtly. It requires comprehensive knowledge and technical skill. With the popularity of buying glasses online, a number of websites have come up with do-it-yourself measurements or apps that will take this measurement for you. The problem is that these are not scientifically accurate measurements and are not being performed by professionals. There is a large margin of error and buyers could end up with glasses that hurt their vision—not correct it.This research is aimed to show ideal procedure that must be committed in producing glasses to avoid inacurate PD measurement. The researcher uses library aprroach to gain related data and informations, then discuss the problem and solution in descriptive approach.